Mitigating housing glut: an application to the Malaysian housing market - Chee, Yin Yip; Senadjki, Abdelhak; Hui, Nee Au Yong; Abdul Adzis, Azira (Emerald Publishing Limited, 2020)
Purpose – This paper aims to construct a model procedure to mitigate housing glut by using both qualitative and quantitative approach. The model applied in the Malaysian context analyzes the following: information contained in media articles and reports issued by Bank Negara Malaysia (BNM) on the housing market to extract the true picture of the housing glut issue; the relative impact (effectiveness) of housing affordability, housing prices and economic growth in influencing housing glut, and how it can be overcome so that appropriate preferential policies can be taken to mitigate the problem. Design/methodology/approach – This study uses quarterly data from 2000 to 2017 to conduct economic analysis, economic theory analysis and cointegrating regression, whereas information from mediapublished housing articles and reports issued by BNM are examined and interpreted to draw the true picture of housing glut.Findings – The results obtained from quantitative analysis show that housing affordability exerts very mild relative effect (0.0097) negatively on housing glut, whereas economic growth and housing price produce a relatively mild positive impact of (0.020) and (0.022), respectively, conflicting to the common consensus that the two factors have a significant effect on housing glut. Qualitatively, the results of this study show that housing glut seems to be relatively larger for affordable housing, which is contrary to the quantitative results, pointing to the existence of other influencing factors. Research limitations/implications – There is an imperative need for a third-party survey to gain a comprehensive understanding of the market conditions and buyers’ sentiment and preference. Originality/value – This study compares both quantitative and qualitative results with expected housing market movements and responses based on conventional wisdom.